PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP HARGA SAHAM PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Fahmi, Muhammad; Purmawan, Herry (Balance : Jurnal Akuntansi dan Bisnis, 2017)
The aim of this study is to know the affect of Corporate Social Responsibility Disclosure toward stock prices of mining companies registered on the Indonesia Stock Exchange 2012-2016. This study is an ex post facto study, the sample of this study were 95 companies annual reports. The data in this study was obtained by study documentation method. Data analysis method used was an analysis of multiple regression. The results showed that (1) Economic Disclosure in Corporate social Responsibility Disclosure affected significantly on stock prices , (2) Environment Disclosure in Corporate Social Responsibility Disclosure didn’t affect significantly on stock prices, (3) Social Disclosure in Corporate Social Responsibility Disclosure didn’t affect signifacantly on stock prices, (4) Economic Disclosure, Environment Disclosure, Social Disclosure in Corporate Social Responsibility Dsiclosure simultaneously affected significantly on stock prices.